PENELUSURAN LIRIK ISLAMI LAGU KAWIH SUNDA 'KUDU KASAHA' KARYA WINARYA ARTADINATA - Solihin, Asep (Paraguna, 2015)
'Kudu  Kasaha' is the song  title or rumpaka written by Winarya Artadinata. The theme  of the lyrics  conveys a mindset  based  on  religious  ideology, Islam. It's the result  of the resignation facing complaints, fluctuation and uncertainty  offaith. If it is listened deeply, the  lyrics  reminds the listeners to  submit   the  complaints  and  uncertainties of faith  in  God Almighty. Moreover,  the choice ofwords is composed in the  literary  mindset. The lyric of 'Kdu Kasaha', thus, isthe morals of religion and  art.